Eksternalitas Bisnis Thrifting dengan Metode Cost and Benefit Analysis di Kota Denpasar (Lembaga Pengembangan Kinerja Dosen, 2025)
Thrifting, or the importation of second-hand clothing, has become increasingly popular, but it poses several issues, not only violating regulations but also threatening the existence of small textile and garment industries, including home-based businesses. Second-hand clothing imported into Indonesia is often classified as waste in its country of origin, and in many cases, not all of it is suitable for use. This makes second-hand clothing a significant source of additional waste for Indonesia. The unsuitability of these garments becomes a major issue as it contributes to the growing volume of waste, which in turn burdens the waste management system and negatively impacts health and the environment. Externalities, which refer to the unaccounted-for impacts of an activity on the welfare of others, are a key issue in the context of the thrifting business. Cost-Benefit Analysis (CBA) is used to measure the costs and benefits of an activity for society. This study aims to analyze the negative externalities caused by the thrifting business, particularly in relation to the waste generated from unsold second-hand clothing. Direct interviews and CBA were employed to compare the externalities generated by thrifting with those of local garment businesses, such as streetwear (distro). The results of the study show that the thrifting business generates more negative externalities compared to the streetwear business. The thrifting business produces significant amounts of unsold clothing, with an average of hundreds of unsold pieces per month. This waste adds to the burden of waste management in Denpasar City. In contrast, the streetwear business has smaller negative externalities, mainly consisting of leftover production materials, which are more controlled and proportionate due to the planned nature of production. Thus, although both sectors have negative impacts, the negative effects generated by the thrifting business are much larger and harder to manage.